Heat Stress Exposure and Chronic Kidney Disease in Indonesian Rayon Factory Workers - Suraya, Anna; Ningsih, Sri Utami; Lelitasari, Lelitasari; Sulandari, Uci; Shanmugam, Rekha; Venugopal, Vidhya (Faculty of Medicine, Universitas Padjadjaran, 2025)
Chronic kidney disease (CKD) has become an emerging occupational health concern, particularly among workers exposed to high temperatures. This study aimed to determine the prevalence of CKD among workers in a rayon factory in West Java, Indonesia, and evaluate its association with occupational heat exposure. A retrospective cohort study was conducted using secondary data from the company’s annual medical check-up records (2022–2023) and workplace heat stress measurements obtained in 2017 using the Quest Temp Wet-Bulb Globe Temperature monitor. Workers who completed medical examinations in both years and gave written informed consent to participate in the study were included. CKD was defined as a serum creatinine level >1.2 mg/dL and an estimated glomerular filtration rate <60 mL/min/1.73 m² in two consecutive years. Chi-square tests were used for bivariate analysis, and multivariate logistic regression was performed to obtain adjusted odds ratios (ORs). Of 675 eligible workers, male constituted the majority (99.7%) and 49% were older than 40 years. Most workers (96.1%) were exposed to workplace temperatures above 28°C, and obesity (47%), hypertension (16.7%), and diabetes mellitus (5.5%) were common comorbidities. The prevalence of reduced kidney function was 5.5%, with heat exposure of 28.2–30°C associated with an OR of 4.5 (95% CI: 1.372–14.792). The prevalence of CKD was 0.9%, and heat exposure in the same temperature range demonstrated an OR of 8.958 (95% CI: 1.207–66.515). However, the association was not statistically significant after adjusting for age, obesity, and hypertension. These findings suggest that occupational heat exposure may contribute to early kidney impairment, highlighting the need for heat mitigation strategies and routine worker health monitoring in industries where workers are at risk of heat exposure.